Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1016/j.neuroscience.2010.05.053
|View full text |Cite
|
Sign up to set email alerts
|

Steroid receptor coactivator-2 expression in brain and physical associations with steroid receptors

Abstract: Estradiol and progesterone bind to their respective receptors in the hypothalamus and hippocampus to influence a variety of behavioral and physiological functions, including reproduction and cognition. Work from our lab and others has shown that the nuclear receptor coactivators, steroid receptor coactivator-1 (SRC-1) and SRC-2, are essential for efficient estrogen receptor (ER) and progestin receptor (PR) transcriptional activity in brain and for hormone-dependent behaviors. While the expression of SRC-1 in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
32
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 127 publications
(185 reference statements)
6
32
0
Order By: Relevance
“…Thus, the latter dose was used in further experiments. Incidentally, it should be noted that concentrations in the high-nM range have been largely used to investigate gene transcriptional regulation by E 2 [23][24][25][26][27] or metabolic effect of this hormone [28]. Moreover, it has been shown that intratesticular concentrations are much higher than serum levels of E 2 [29].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the latter dose was used in further experiments. Incidentally, it should be noted that concentrations in the high-nM range have been largely used to investigate gene transcriptional regulation by E 2 [23][24][25][26][27] or metabolic effect of this hormone [28]. Moreover, it has been shown that intratesticular concentrations are much higher than serum levels of E 2 [29].…”
Section: Resultsmentioning
confidence: 99%
“…In support of this idea, ER and other steroid receptors have distinct affinities for nuclear receptor coactivators. For example, SRC-1 and SRC-2 from the rat hypothalamus and hippocampus physically associate with ER and PR in a receptor subtype- and brain region-specific manner [58,65]. Interestingly, SRC-1 from the hypothalamus interacts more with ERα than ERβ, while SRC-2 associates with ERα but shows virtually no interaction with ERβ [58,65].…”
Section: Discussionmentioning
confidence: 99%
“…For example, SRC-1 and SRC-2 from the rat hypothalamus and hippocampus physically associate with ER and PR in a receptor subtype- and brain region-specific manner [58,65]. Interestingly, SRC-1 from the hypothalamus interacts more with ERα than ERβ, while SRC-2 associates with ERα but shows virtually no interaction with ERβ [58,65]. In addition, receptor-coactivator interactions are influenced by different ligands and response elements on DNA [90,91,92,93].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations